2023
DOI: 10.1101/2023.10.14.562343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network analyses reveal D clade ethylene response factors as major regulators of jasmonic acid-mediated resistance to early blight disease complex in tomato

Christopher Tominello-Ramirez,
Lina Muñoz Hoyos,
Mhaned Oubounyt
et al.

Abstract: Resistance mechanisms to early blight disease complex (EBDC) in tomato remain obscure given its polygenic and quantitative nature. We investigated the early defense responses of Heinz 1706 tomato to EBDC using RNA-seq. We observed distinct transcriptional reprofiling upon exposure to two EBDC isolates and the PAMP chitin. Avirulent isolate CS046 (Alternaria alternata) elicited a vigorous defense response in the host, whilst the virulent isolate 1117-1 (Alternariasect.Porri) showed subdued gene expression, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…Transcriptomics studies in the A. solani /potato pathosystem have highlighted the induction of peroxidases, terpene synthases, and JA/ET biosynthesis genes during EBDC infection, but questions remain about how a resistant cultivar is significantly more resistant than a susceptible cultivar (Sajeevan et al., 2023 ). We found that tomatoes treated with avirulent EBDC‐induced expression of D clade ethylene response factors (ERFs) that were highly influential in both co‐expression and gene regulatory networks associated with JA/ET biosynthesis, secondary metabolite biosynthesis and their transporters, detoxification, and calcium signalling (Tominello‐Ramirez et al., 2023 ). Conversely, tomatoes treated with virulent EBDC induced far fewer genes and no clear defence, either SA‐ or JA‐mediated.…”
Section: Host Defencementioning
confidence: 99%
“…Transcriptomics studies in the A. solani /potato pathosystem have highlighted the induction of peroxidases, terpene synthases, and JA/ET biosynthesis genes during EBDC infection, but questions remain about how a resistant cultivar is significantly more resistant than a susceptible cultivar (Sajeevan et al., 2023 ). We found that tomatoes treated with avirulent EBDC‐induced expression of D clade ethylene response factors (ERFs) that were highly influential in both co‐expression and gene regulatory networks associated with JA/ET biosynthesis, secondary metabolite biosynthesis and their transporters, detoxification, and calcium signalling (Tominello‐Ramirez et al., 2023 ). Conversely, tomatoes treated with virulent EBDC induced far fewer genes and no clear defence, either SA‐ or JA‐mediated.…”
Section: Host Defencementioning
confidence: 99%